MESSAGE GUIDED RANDOM AUDIO STEGANOGRAPHY USING MODIFIED LSB TECHNIQUE - Jangra, Taruna; Singh, Dr. Dinesh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Steganography is the science of hiding secret data in such a way that its presence can’t be noticed. Techniques which hide more secret data in cover files and which doesn’t affect transparency of cover signal are better one for steganographic purpose. In the proposed technique which keyless randomization is provided to insert secret information in multiple and variable LSBs. Cover signal is converted into binary format and then with the proposed algorithm binary cover signal is divided into blocks of size 8x8 with 16 bits per sub block, and then checking each sub blocks first two MSBs to find how many LSBs will be used for insertion of secret data bits. PSNR values show that there is no noticeable difference between cover audio signal and stego audio signal. Security increases due to the use of variable number of LSBs for insertion and keyless randomization are provided by counting out technique.